The rignts of litigants in employment dispute resolution on Malaysia - Kamal Halili Hassan, (Fakulti Undang - Undang, 2007)

(untitled)
This article discusses the tights of litigants in the course or their actions in seeking remedies form various employment dispute resolution institutions, in particular the Industrial Court. The rights discussed here emanated from and provided by the law – constitutional and statutory – and affirmed by the courts. There are several rights discussed in the article such as the right to adjudication, representation, plead mitigation and remedies. Except on the issue of the right to plead mitigation where reliance is made on the right of litigation in public service, the other rights centre on workers employed in the private sector. This article also demonstrates a statistic on factors of trade disputes referred to the Ministry of Human Resource. Workers in Malaysia do enjoy several rights in the sphere of their employment and especially so when they seek remedies from the Courts